Influence of angiotensin II receptor subtypes of the paraventricular nucleus on the physiological responses induced by angiotensin II injection into the medial septal area - Saad, Wilson Abrão [UNESP]; De Arruda Camargo, Luiz Antonio (FapUNIFESP (SciELO), 2003)
Objective - We determined the effects of losartan and PD 123319 (antagonists of the AT1 and AT2 angiotensin receptors, respectively), and [Sar1, Ala8] ANG II (a relatively peptide antagonist of angiotensin receptors) injected into the paraventricular nucleus (PVN) on water and 3% NaCl intake, and the diuretic, natriuretic, and pressor effects induced by administration of angiotensin II (ANG II) into the medial septal area (MSA) of conscious rats. Methods - Holtzman rats were used. Animals were anesthetized with tribromoethanol (20 mg) per 100 grams of body weight, ip. A stainless steel guide cannula was implanted into the MSA and PVN. All drugs were injected in 0.5-μl volumes for 10-15 seconds. Seven days after brain surgery, water and 3% NaCl intake, urine and sodium excretion, and arterial blood pressure were measured. Results - Losartan (40 nmol) and [Sar1, Ala8] ANG II (40 nmol) completely eliminated whereas PD 123319 (40 nmol) partially blocked the increase in water and sodium intake and the increase in arterial blood pressure induced by ANG II (10 nmol) injected into the MSA. The PVN administration of PD 123319 and [Sar1, Ala8] ANG II blocked whereas losartan attenuated the diuresis and natriuresis induced by MSA administration of ANG II. Conclusion - MSA involvement with PVN on water and sodium homeostasis and arterial pressure modulation utilizing ANGII receptors is suggested.
Keywords: Blood pressure; Central nervous system; Sodium balance; 1 (4 dimethylamino 3 methylbenzyl) 5 diphenylacetyl 4,5,6,7 tetrahydro 1h imidazo[4,5 c]pyridine 6 carboxylic acid; angiotensin II; bromethol; losartan; receptor subtype; sodium chloride; stainless steel; angiotensin receptor; antihypertensive agent; imidazole derivative; pyridine derivative; saralasin; sodium; vasoconstrictor agent; animal experiment; animal model; animal tissue; arterial pressure; attenuation; blood pressure measurement; body weight; brain surgery; cannula; controlled study; diuresis; fluid intake; male; measurement; natriuresis; nonhuman; rat; septum pellucidum; sodium excretion; sodium intake; thalamus midline nucleus; urinary excretion; animal; anterior hypothalamus; blood pressure; drinking; drug antagonism; drug effect; homeostasis; metabolism; Sprague Dawley rat; Angiotensin II; Animals; Antihypertensive Agents; Blood Pressure; Diuresis; Drinking; Homeostasis; Imidazoles; Losartan; Male; Paraventricular Hypothalamic Nucleus; Pyridines; Rats; Rats, Sprague-Dawley; Receptors, Angiotensin; Saralasin; Septum of Brain; Sodium; Vasoconstrictor Agents